Penny for Your Preferences: Leveraging Self-Expression to Encourage Small Prosocial Gifts - Rifkin, Jacqueline R.; Du, Katherine M.; Berger, Jonah (Journal of Marketing, 2021)
Prior approaches that leverage identity to motivate prosocial behavior are often limited to the set of people who already strongly identify with an organization (e.g., prior donors) or by the costs and challenges associated with developing stronger organization-linked identities among a broader audience (e.g., encouraging more people to care). In contrast, this research demonstrates that small prosocial gifts, such as tips or small donations, can be encouraged by framing the act of giving as an opportunity to express identity-relevant preferences—even if such preferences are not explicitly related to prosociality or the organization in need. Rather than simply asking people to give, the “dueling preferences” approach investigated in this research frames the act of giving as a choice between two options (e.g., cats vs. dogs, chocolate vs. vanilla ice cream). Dueling preferences increases prosocial giving by providing potential givers with a greater opportunity for self-expression—an intrinsically desirable opportunity. Seven experiments conducted in the laboratory, online, and in the field support this theorized process while casting doubt on relevant alternatives. This research contributes to work on self-expression and identity and sheds light on how organizations can encourage prosocial behavior.